PENGARUH INTENSITAS MODAL, PERTUMBUHAN PENJUALAN DAN KEPEMILIKAN MANAJERIAL TERHADAP PENGHINDARAN PAJAK - Rahmahdanti, Ananda; Yazid, Abu (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
This study aims to determine and analyze the effect of Capital Intensity, Sales Growth and Managerial Ownership on Tax Avoidance in primary food and beverage consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2019 to 2023. This type of research is quantitative research, using secondary data. The data analysis method used is the panel data regression test using the Microsoft Excel and E-Views 12 applications. The population in this study were primary consumer goods sector companies listed on the Indonesia Stock Exchange for the period 2019 to 2023. The data collection technique in this study was purposive sampling technique with the results of 125 research populations into 10 research samples processed in this study. The results showed that capital intensity, sales growth and managerial ownership simultaneously affect tax avoidance. And partially states that sales growth has a persial effect on tax avoidance. While capital intensity and managerial ownership have no effect on tax avoidance. Keywords : Capital Intensity, Sales Growth., Managerial Ownership, Tax Avoidance